Preservation of red blood cell antigenicity in a new storage solution in vitro. (31st December 2023) - Tang, Sheng-Hui; Lin, Hsin-Chung; Chang, Jin-Biou; Chan, Yung-Shu; Tang, Hui-Fei; Chang, Feng-Yee; Chiueh, Tzong-Shi; Yang, Bing-Heng
Abstract: Introduction: Red blood cell (RBC) storage solution is used for suspending and preserving RBCs for later use in in vitro immunohematology testing. Proper RBC preservation is crucial for obtaining accurate results in RBC phenotyping and pretransfusion antibody screening tests. Haemolysis or RBC antigen degradation during storage can result in inaccurate RBC phenotyping, thereby decreasing the sensitivity of pretransfusion antibody screening and identification assays. The conventional RBC storage solutions usually contain adenosine, adenine, and antibiotics. We designed an RBC storage solution and determined whether it could preserve RBC integrity for 70 days. Materials and Methods: The new storage solution has a different formula from that of the conventional solution—in particular, it is strengthened with polyethylene glycol (PEG). The extent of haemolysis and hemagglutination reactivity of the RBC antigen systems, Rh, Duffy, Kidd, Lewis, MNS, P1, and the rare antigen Mi a (which has a low prevalence antigen in most parts of the world but a higher prevalence in Taiwan), in the new RBC storage solution was compared with that of the conventionally preserved RBC storage solution. Results: The RBCs preserved in the new solution for 70 days retained a similar haemolysis grade as those preserved in the control solution for 28 days. Although both solutions largely preserved RBC antigenicity, the decline in RBC hemagglutination scores in new solution often occurred later than that in the control solution in most antigen phenotyping assays, especially labile antigens such as D, P1, and M. Conclusion: The new solution reduces haemolysis more effectively and preserves antigenicity throughout the 70-day storage period. Moreover, Mi a antigen is more stable in the experimental group.